CSF ANALYSIS AND THE DIAGNOSIS OF NEUROMYELITIS OPTICA. Issue 11 (9th October 2013) - Luppe, Sebastian; Robertson, Neil
Abstract : Objective: Neuromyelitis optica (NMO) is a distinct disorder with recognizable clinical radiological and immune characteristics. Whereas cerebrospinal fluid (CSF) examination has an established role in the diagnosis of other CNS inflammatory disorders including Multiple Sclerosis (MS), data for NMO is scarce and where available frequently predates availability of testing for anti–Aquaporin 4 antibodies (AQP4–IgG) that now form an essential component of the diagnostic process. In this study we have examined disease course and CSF characteristics in a population–based cohort of patients with seropositive NMO. Methods: From June 2011 to January 2013, we identified 42 cases of NMO, fulfilling Wingerchuk 2006 revised diagnostic criteria and testing positive for AQP4–IgG. We enrolled these patients into a retrospective case series with longitudinal follow–up and systematically collected clinical and laboratory data through patient visits and review of computer and paper records. CSF analyses were performed as part of routine clinical investigations on these patients in 15 NHS hospitals between December 1987 and February 2012. Results: Data on 66 CSF samples from 33 patients were available. Thirteen patients (39%) had a single lumbar puncture and 21 patients 2 or more (range 1–6). 74% of samples showed≥1 abnormality, this increased to 87% for the samples obtained within 30 days of a relapse. White cell pleocytosis (predominantly lymphocytic), of >5 cells/ml (range 6–190) was found in 48%, >15 cells/ml in 27%, and >50 cells/ml in 7% of samples. A CSF Pleocytosis of >5 cells/ml was seen in 54% samples obtained within 30 days of a relapse, compared to only 20% in samples obtained after this time. CSF protein was raised (range 0.46–2.1 mg/dl) in 52%, and was ≥0.7 mg/dl in 28%, and ≥1.0 mg/dl in 11% of samples. CSF protein was raised in 63% samples obtained within 30 days of relapse compared with only 27% obtained at a greater time interval from relapse. CSF glucose (range 2.3–6.0 mmol/l) and matched CSF/serum glucose ratios (0.4–0.9) were within normal range in all samples. Oligoclonal band (OCB) status was positive in 23/56 (41%) of samples (48% neg, 9% paired, 2% equivocal). OCBs were more likely to be positive within the first 12 months of disease onset (48%), than after that time (42%). In addition dynamic change in OCB status over time was observed in 5/14 (36%) but remained unchanged in 9/14 (64%). Conclusion: White cell pleocytosis was the most frequent abnormality (48%) followed by raised CSF protein (54%) and positive OCBs (41%) and were most commonly observed within 30 days of relapse. Cell counts of >50/ml and CSF protein of >1.0 g/dl, contrary to popular belief, were unusual. In addition CSF changes in NMO were frequently dynamic and likely to relate to recent disease activity. Whilst these changes may be useful in monitoring some aspects of disease activity OCBs should not be employed to discriminate between NMO and other neuroinflammatory disorders and in particular MS, and also challenge the concept that development of positive OCB status is irreversible.